Pengaruh Profitabilitas Dan Solvabilitas Terhadap Income Smoothing Dengan Good Corporate Governance Sebagai Variabel Moderating Pada PT. Bank Muamalat Indonesia Tbk - Febiyanto; Karnila Ali; Siti Khoiroh (Universitas Muhammadiyah Metro, 2024)
This study aims to determine whether profitability (ROA), solvency (DER), and good corporate governance are able to moderate the effect of profitability (ROA) on income smoothing at PT.Bank Muamalat Indonesia Tbk. To find out whether Good Corporate Governance is able to moderate the effect of solvency (DER) on income smoothing at PT. Bank Muamalat Indonesia Tbk. This research is a descriptive quantitative research by collecting data through financial reports at PT Bank Muamalat Tbk for the 2019-2021 period. The data collection technique uses a documentation study by collecting financial reports and aspects related to research variables. Technical data analysis was carried out using descriptive statistics presenting data in the form of average data, minimum values, maximum values, and standard deviation of each variable studied. This research will present the required data, namely profitability ratios, solvency ratios, Good Corporate Governance, and income smoothing. These data were obtained from the sample to be examined, namely the financial statements of PT. Bank Muamalat Indonesia Tbk in 2019-2021. This study also uses the Partial Least Square (PLS) statistical technique. PLS analysis is a multivariate statistical technique by comparing the multiple independent variables and multiple dependent variables. The results of this study indicate that Profitability (ROA), Solvability (DER) have a positive effect on income smoothing at PT. Bank Muamalat Indonesia Tbk, GCG can moderate the effect of profitability (ROA) and solvency (DER) on income smoothing at PT. Bank Muamalat Indonesia Tbk.